Management Model of Reef Fisheries in Karimunjawa National Park - Ririn Irnawati; Domu Simbolon; Budy Wiryawan; Bambang Murdiyanto; Tri Wiji Nurani (Forum Pasca Sarjana, 2012)
Karimunjawa National Park (KNP) inhabited mostly by fisherman. Its area surrounds by 111.625 ha as waters. Fishing zone is dedicated for traditional fisheries. Therefore the capture fisheries in KNP should be adjusted to ccommodate conservancy and utilization objectives. The objective of the research is to design management model of reef fisheries in KNP. Selection of leading fish product was conducted by implementing comparative performance index. Potency of reef fish resources was performed by using bio-economic model. Optimization number of fishing gear is performed by using LGP. Feasibility study for fishery business was conducted with R/C, ROI, PP, NPV, B/C, and IRR criteria. Policy and institutional for capture fisheries was conducted by using institutional analysis. The result shows the leading fish from reef fish is jack trevallies and yellow tail; reef fish potency is 174.225,68 kg/year; the fishing technology for reef fish are hand line (1.412 units) and traps (102 units); hand line, fish trap, and muroami are competent to develop continuously in KNP area; the policy of reef fisheries need to coordinate between stakeholders and institutions to gain optimal management; the institutional that involve in management are fishermen group, BTNKJ, DKP, NGO, fisherman’s business group, and educational institutions.